Sharing Of Critical Teaching Incidents In A Tesol Practicum Using Facebook - Naidu, Paramisvari Rama (2020)
Practicum is attributed as the core component in any Teacher Education programmes. The PSTs are expected to transform the knowledge gained in the theoretical part into practice. Recent literature reveals that the PSTs are experiencing severe contextual restraints on daily basis during practicum. They experience incidents that become turning points in their teaching lives and are deemed as ‗critical‘. These are termed ‗critical teaching incidents‘ (CTIs). This research seeks to find out; (1) to find out the CTIs experienced by the TESOL PSTs during their practicum, (2) to investigate the consequences encountered due to the CTIs experienced by the TESOL PSTs during their practicum and (3) to examine the usefulness of Facebook as a platform to share the CTIs in their TESOL practicum. A number of 10 final year TESOL PSTs took part in this research. The artefacts from Facebook, reflective journals and online structured interviews provided the opportunity to access the PSTs professional landscape to reveal the CTIs experienced in practicum. The use of multiple analysis approaches provided different lenses to interpret the CTIs. A Qualitative research method was employed in this research to gather the data for duration of two months. The data was analyzed using Braun and Clark‘s thematic approach. Students‘ negative attitude, lack of commitment, use of mother tongue, poor proficiency and external factors are the CTIs identified in this research. The results also revealed the consequences of CTIs faced by the PSTs; lost motivation and ineffective lesson planning. The results also indicated that, using Facebook to share the CTIs during practicum enables the TESOL PSTs to conduct effective teaching, exchange ideas, promote teamwork and collaboration to address the CTIs as a CoP. This has generated several theoretical, pedagogical and policy implications for the teacher education institutions, universities and researchers, Therefore, it can be concluded that sharing of CTIs in a TESOL practicum using Facebook would improve the TESOL PSTs potentialities and develop their teaching ability.